Epidermal structure of Pinanga coronata (Blume ex Mart.) Blume (Palmae) in Java and Bali - JOKO R. WITONO (Society for Indonesian Biodiversity, 2003)
Pinanga coronata is one of palms species that has complex characters in morphology, because distribution of the species isvery diverse. In the wild, P. coronata is found throughout Java and Bali, occuring on lowland forest to montane forest at altitude 1.900 m asl. This paper presents leaf anatomy observation on 21 samples from different localities and altitudes throughout Java and Bali. Observation results show that all samples have simillar form and structure of epidermis cells and stomata, so the results gave evidence that leaf anatomy observation has simillar results with morphological observation of this species.Â© 2003 Jurusan Biologi FMIPA UNS SurakartaKey words: leaf epiderm structure, Pinanga coronata, Java, Bali